Japanese type cardiomyopathy associated with preexcitation / Japanese type cardiomyopathy without deep negative T waves and with findings of preexcitation on ECG - (:unkn) unknown (My University, 2010)
0
Preeksitasyon ve Japon tipi kardiyomiyopati birlikteliği / EKG'de derin negatif T dalgaları izlenmeyen, preeksitasyon bulguları izlenen Japon tipi kardiyomiyopati
Keywords: Kalp ve Kalp Damar Sistemi